Lexical features of the modern turkish language: instructional techniques of introducing vocabulary at the lessons of the turkish language and typical mistakes in students' speech - Shafigullina, Liliya Shamilovna (Universidade Estadual Paulista, 2021)
The relevance of the problem under research is determined by the need to perfect the methods of teaching the Turkish language to university students. The aim of the article is to thoroughly characterize the lexical features of the Turkish language and analyze teaching techniques of preface of lexical material at the lessons of the Turkish language to university students. The leading approach to the study of this problem is a problem-thematic advance. The key findings of research are systematization of lexical features of the Turkish language, lexical analysis of typical mistakes in the speech of students at the original stage of learning the Turkish language. The basic elements of the methodology of studying the Turkish language by the students in Russian universities have been presented. The method of working with lexical units of the Turkish language in the student auditorium has been designed. An overview of typical mistakes made by students whereas learning a Turkish lexical unit has been presented. The materials of the article may be useful for teaching the Turkish language at universities of the Russian Federation, conducting also experiments to test the effectiveness of these methodological advances, as well as developing more effective tasks in order to form good skills of speaking Turkish.